Character Building Through Qur'anic Education: A Study of TPQ Al-Aziz in Lengkong Village, Mojoanyar - Dewi , Nurna Kurnia; Mujiono; Nur Kholis, Muhammad Maulana (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Qur’an education park Al Aziz has more than 100 students and 7 permanent teachers with several program activities which are very many activities such as daily activities, spontaneous activities, exemplary activities and annual activities so that they can shape the character of students in students. -Qur'an (Tpq) Al-Aziz, Lengkong Village, Mojoanyar, Mojokerto. The focus of this research on 1). What is the process of forming the character of the students in the Al-Aziz Al-Qur'an Education Park (TPQ), Lengkong Village, Mojoanyar, Mojokerto? 2). What are the results of the formation of the character of the students in the Al-Aziz Al-Qur'an Education Park (TPQ), Lengkong Village, Mojoanyar, Mojokerto? By using a qualitative type approach. Through several activities that have been carried out by students through several programs contained in TPQ Al Aziz, students have the character of santri as follows: 1). Students have an increase in piety to Allah SWT. Students get this through all existing activities such as reciting the Koran, praying, and praying in congregation. 2). Students have a sense of gratitude that students get with a little increase in reading the Koran. 3). Students have a sincere nature. 4). Students have patience. 5). Qonaah. 6). Laughter. Student trust is seen from the sincerity and enthusiasm of students in carrying out the process of educational activities at TPQ Al Aziz